The Siege of Razama - An example of aggressive defence in Old-Babylonian times - Vidal, Jordi (Altorientalische Forschungen, 2009)
This paper analyses the aggressive defence practised by the inhabitants of Razama during the siege of the city by an army led by Atamrum in 1765 BCE, as it is described in several Mari texts. Special attention is payed to the reconstruction of the defensive action described in ARM 14 104 + , a text which reflects the expertise of the Razameans in this kind of military action as well as the inability of the besiegers to counteract it.